Breast cancer: updates and advances in 2016. Issue 1 (February 2017) - Giordano, Sara B.; Gradishar, William
Abstract : Purpose of review: Approximately 1 in 8 US women (12%) will develop invasive breast cancer over the course of her lifetime. In 2016, an estimated 246, 660 new cases of invasive breast cancer are expected to be diagnosed and approximately 40, 450 would die as a result of it. The global burden of breast cancer exceeds all other cancers and the incidence is increasing. The heterogeneity of breast cancer makes it a challenging solid tumor to diagnose and treat. This review focuses on the recent advances in breast cancer therapy including hormonal treatment of metastatic breast cancer, targeting cyclin-dependent kinases (CDK) 4/6 in breast cancer, updates in targeting human epidermal growth factor receptor 2 (HER2) positive breast cancer, adaptive randomization trial design and cancer genetic risk assessment. Recent findings: Breast cancer is a heterogeneous disease and targeted therapy is improving the outcomes of women. The use of cyclin-dependent kinase inhibitors (CDK) 4/6 have demonstrated a substantial improvement in progression-free survival in the first line setting of metastatic hormone receptor positive breast cancer. And newer agents directed at HER2 continue to revolutionize HER2-positive breast cancer treatment. Summary: This review highlights the recent updates in breast cancer treatment, new concepts in clinical trial design and provides a current overview of cancer genetic risk assessment.